Navigating The Bind of Necessary Evils: Psychological Engagement and The Production of Interpersonally Sensitive Behavior - Margolis, Joshua D.; Molinsky, Andrew (Academy of Management Journal, 2008)
We develop grounded theory about how individuals respond to the subjective experience of performing “necessary evils” and how that influences the way they treat targets of their actions. Despite the importance and difficulty of delivering just, compassionate treatment when it is most needed—when necessarily harming another person—little research has focused on those who must do so. Using qualitative data from 111 managers, doctors, police officers, and addiction counselors, we document how performers both engage and disengage when doing these tasks, unearth multiple forms of interpersonal justice, and identify four styles of response for handling necessary evils.